FOSTERING THE CHARACTER OF LOVE FOR THE HOMELAND THROUGH THE SMART CARD LEARNING MEDIA IN ELEMENTARY SCHOOLS - Zainuddin, Zainuddin; Shiddiq, Ahmad; Agustina, Putri (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
The application of character in the school environment still needs to be developed further. This research tries to implement character values into the learning process. Learning is designed according to syntax containing the character of love for the homeland through smart card media. This type of research is qualitative descriptive research. The informants involved in this research were the principal, class V teacher, and class V students at Elementary School (ES) Baban I Sumenep, East Java, Indonesia. The data collection technique in this research is using questionnaires and observation. The data analysis technique used is a descriptive statistical analysis to obtain the percentage value of student activity toward character learning treatment. These findings show that student activity was 85% of Observer I and 88.5% of Observer II with very good criteria. The percentage of questionnaire scores obtained after character learning was 82.6%. Before character learning was carried out, the questionnaire score percentage was 72.4%. Developing the character of love for the homeland through smart card learning media can optimize a sense of courtesy, mutual respect between others, and mutual love and appreciation for the services of heroes.